(3WHbGJ GdeaSQjfs - (3CMeO Hf eMeOs
(3ChdgG (B:s
(3GdMeO ddg GdPi HfYeJg JJe GdUGdMGJ, hHPcQ YdeGFg hChdjGFg JfRd GdHQcGJ , hGdSdGI Ydi CTQa GdeNdhbGJ s
(3BNQgG (B:s
(3GdMeO ddg Ydi GdEJeGe hGdENJJGe Yf JQJjH gPg GdWHbGJ HCMSf GdfXGe aj Gdjhe GdYGTQ ef TgQ LeGOi GdChd SfI EKfJjf hJSYjf hCda Ydi jO LGeYI hcGJHg CMeO Hf eMeO s
(3HChdgG agQS ddoeJQLejfs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B281 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs